Experiências no ensino das Artes Visuais : a fotografia artística em Chapecó - Monari, Ana Claudia (2018)
This article presents actions developed in the compulsory stage for undergraduate degree in Visual Arts, at a community university in the West region of Catarinense / Brazil. The practices were developed with the intention of working local artists and their photographic productions within a historical / cultural context